Assessment on Geography Field study at Universities in Indonesia - Aris Munandar; Enok Maryani; Dede Rohmat; Mamat Ruhimat (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2019)
In Geography Study Program, fieldstudy is the hallmark of geography outdoor learning. The similar activities of fieldstudy are fieldwork, fieldtrip, outing, excursion, cooks tours and others. The implementation of fieldstudy in the universities of teacher training has the similarity in its naming, its definition, its purpose, material of the study, the duration of the activity, the location of the fieldstudy, and data processing. The difference of the fieldstudy implementation lies on the ratio of supervisor to students, funding, outcome product and assessment. Universities that conduct the fieldstudy should review the curriculum in its implementation so that the credit, the assessed product and process have the similarity both in the credit and the supervisors who assess.